Identification of a postoperative survival scoring index for adult liver transplantation - Shuai Wang; Xiaohong Lin; Yefu Li; Zhonghao Xie; Ming Zhang; Yicheng Liang; Chuchen Zhu; Yuqi Dong; Ping Zeng; Xiaoshun He; Weiqiang Ju; Maogen Chen (Annals of Medicine)
Background In addition to surgical technology, successful liver transplantation (LT) depends on perioperative management, which needs an effective prognostic index. Therefore, a simplified and sensitive postoperative index for adult LT should be developed.Methods In total, 906 patients who underwent LT were included in this cross-sectional study. Univariate analysis was used to identify the independent risk factors for recipient survival. Multivariate logistic and stepwise regression analyses were used to construct and simplify the model design. Area under the curve (AUC) and Kaplan–Meier’s (K–M) analysis demonstrated superiority of the new index. The postoperative survival score (POSS) index was further simplified via restricted cubic spline (RCS) analysis. Finally, the interpretation of the long-term mortality and subgroup analyses extended the application of the POSS index.Results Finally, a total of five factors (donor sex, recipient body mass index (BMI), total bilirubin (Tbil), international normalized ratio (INR) and total operative time) were identified as independent risk parameters and included in our POSS index. The AUCs of the original and simplified POSS indices were 0.764 and 0.723, respectively. Patients with high scores had poor short-term survival. Our index also functioned well in predicting long-term mortality, and it was more effective for patients with hepatitis B cirrhosis or hepatocellular carcinoma (HCC).Conclusions We constructed a simplified and effective postoperative survival scoring index to predict short-term complications and survival in adult LT patients.